Complementary amide-based donor–acceptor with unique nano-scale aggregation, fluorescence, and band gap-lowering properties: a WORM memory device. (20th October 2020) - Ghosh, Tanmoy; Mondal, Somrita; Maiti, Rituparna; Nawaz, Sk Masum; Ghosh, Narendra N; Dinda, Enakshi; Biswas, Amrita; Maity, Suman Kumar; Mallik, Abhijit; Maiti, Dilip K
Abstract: Organic fluorescent semiconducting nanomaterials have gained widespread research interest owing to their potential applications in the arena of high-tech devices. We designed two pyrazaacene-based compounds, their stacked system, and the role of gluing interactions to fabricate nanomaterials, and determined the prospective band gaps utilizing the density functional theory calculation. The two pyrazaacene derivatives containing complementary amide linkages (–CONH and –NHCO) were efficiently synthesized. The synthesized compounds are highly soluble in common organic solvents as well as highly fluorescent and photostable. The heterocycles and their mixture displayed efficient solvent dependent fluorescence in the visible region of the solar spectrum. Notably, the compounds were associated through complementary NHO = C type hydrogen bonding, π–π stacking, and hydrophobic interactions, and thereby afforded nanomaterials with a low band gap. Fascinatingly, the fabricated stacked nanomaterial system exhibited resistive switching behavior, leading to the fabrication of an efficient write-once-read-many-times memory device of crossbar structure.